Evolution of rice consumption and demand patterns - Gyimah-Brempong, Kwabena; Kuku-Shittu, Oluyemisi (University of Pennsylvania Press, 2016)
The chapter begins by highlighting how rice has become a dominant food staple in the Nigerian diet over a relatively short period of time. This is accomplished by examining trends in rice consumption, both on aggregate and per capita terms, over the postcolonial period, including regional and urban/ rural differences. This is followed by a discussion on the possible explanations or determinants of the growth in demand, including a look at local trends in rice prices. Following this, the chapter empirically estimates the behavioral patterns of demand for rice in Nigeria by rural and urban populations and income status. The analysis uses a linear expenditure system demand model and the most recent data from the 2011 Living Standards Measurement Study-Integrated Surveys on Agriculture (LSMS-ISA) (Nigeria, NBS and World Bank 2011), which is the nationally representative household data collected by the World Bank and the NBS. The results of the analysis provide parameter estimates of average budget shares (ABS ) and marginal budget shares (MBS), income, and own- and cross-price elasticities, which can be invaluable for informing future rice policies. A summary and discussion of the key findings from the analysis and their policy implications conclude the chapter.